Knowledge, Abilities, Skills and Its Impact on Business Performance of Business Actors in the Culinary Sector - Nurul Sukriani; Dian Febrina; Diana Sri Dewi (International Journal of Islamic Business and Management Review, 2023)
This study aims to analyze the effect of Knowledge, Abilities, and Skills on the Business Performance of Culinary Entrepreneurs in Pekanbaru City. The data analysis method used is quantitative. Sources of data using primary and secondary in the form of questionnaires and interviews. The population in this study are culinary business actors in the city of Pekanbaru. For the population and sample because the total population is not known with certainty, then a total sample of 97 people. The results of the study indicate that there is a simultaneous significant influence between Knowledge, Abilities, and Skills on the Business Performance of Culinary Entrepreneurs in Pekanbaru City. Partially also found that knowledge has a significant effect on business performance, ability has a significant effect on business performance, skills have a significant effect on business performance.